2013
DOI: 10.1007/s00424-013-1335-8
|View full text |Cite
|
Sign up to set email alerts
|

The organic cation transporter 3 (OCT3) as molecular target of psychotropic drugs: transport characteristics and acute regulation of cloned murine OCT3

Abstract: The organic cation transporter 3 (OCT3) is a widely expressed transporter for endogenous and exogenous organic cations. Of particular interest is OCT3 expression and function in the brain, where it plays a role in serotonin clearance and influences mood and behavior. Protein kinase signaling mediates rapid modulation of cerebral processes, but little is known about acute regulation of OCT3 by protein kinases. Therefore, we cloned mouse OCT3 (mOCT3) and generated a human embryonic kidney cell line stably expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 49 publications
4
33
1
Order By: Relevance
“…The functionality and directionality of organic cation transport was proven by using the fluorescent cation 4-Di-1-ASP. 4-Di-1-ASP was previously shown to be a substrate of OCT2 and OCT3 using HEK293 cells transfected with the respective transporter (Biermann et al, 2006;Cetinkaya et al, 2003;Ciarimboli et al, 2004;Massmann et al, 2014). RPTEC/TERT1 cells took up the dye preferentially from the basolateral side and we could also demonstrate a net transport across the cells to the luminal compartment.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The functionality and directionality of organic cation transport was proven by using the fluorescent cation 4-Di-1-ASP. 4-Di-1-ASP was previously shown to be a substrate of OCT2 and OCT3 using HEK293 cells transfected with the respective transporter (Biermann et al, 2006;Cetinkaya et al, 2003;Ciarimboli et al, 2004;Massmann et al, 2014). RPTEC/TERT1 cells took up the dye preferentially from the basolateral side and we could also demonstrate a net transport across the cells to the luminal compartment.…”
Section: Discussionmentioning
confidence: 85%
“…Several studies have shown ASP to be a substrate for different OCTs and MATE isoforms (Biermann et al, 2006;Cetinkaya et al, 2003;Ciarimboli et al, 2005Ciarimboli et al, , 2004Maekawa et al, 2007;Massmann et al, 2014). RPTEC/TERT1 cells exhibited significantly higher uptake of 4-Di-1-ASP if applied from the basolateral than apical side (p = 0.008, Fig.…”
Section: Tablementioning
confidence: 84%
“…For example, mice lacking both SLC22A1 and SLC22A2 exhibit defective secretion of organic cations by the kidney 109 . SLC22A3 (OCT3) seems to have a key role in neurotransmitter uptake in the nervous system 10,110,111 . OCTNs, which include SLC22A4 and SLC22A5 (also known as OCTN1 and OCTN2, respectively), are highly expressed in muscle and in many other tissues, playing a crucial part in metabolism involving carnitine 10 (TABLE 3).…”
Section: Endogenous Roles Of Drug Transportersmentioning
confidence: 99%
“…Within various cells and structures of the CNS, there are also many SLC and ABC transporters, including those related to the drug transporters discussed here. SLC22A3 (OCT3), for instance, is expressed in the brain, where it is involved in neurotransmitter uptake, and it may be a therapeutic target for certain neuro-psychiatric disorders 111 . Thus, it will be very interesting to trace, in detail, the movement of substrates through the blood–brain barrier–CNS–choroid plexus axis.…”
Section: Endogenous Roles Of Drug Transportersmentioning
confidence: 99%
“…Ketamine and its active metabolite norketamine undergo metabolism via hepatic Cytochrome P450s primarily via CYP2B6 and CYP3A4, which may be impacted with the co‐administration of other pharmaceuticals, such as rifampicin, itraconazole, and ticolpidine, though none of the SOC agents are predicted to have effects on ketamine metabolism . In addition to metabolic clearance, ketamine is a substrate of the rat and human uptake organic cation ion transporters (OCT1, OCT2, OCT3) that mediate biliary and renal elimination of organic bases . It is known that 2‐PAM is a substrate in rats and mice of OCT1 and OCT2, atropine is a potent inhibitor of OCT1 and OCT3, while midazolam is an OCT1 inhibitor .…”
Section: Introductionmentioning
confidence: 99%